Upregulation of miR-140-5p uncouples mitochondria by targeting Bcl-xL in vascular smooth muscle cells in angiotensin II-induced hypertension. Issue 1 (1st January 2022) - Tuo, Buxiong; Xu, Jie; Zhang, Wenqiang; Li, Xiaomiao; Peng, Lijing; Zou, Qian; Deng, Ying; Lei, Junning; Li, Hui
ABSTRACT: Angiotensin II–induced vascular smooth muscle cell (VSMC) remodeling and dysfunction is a major contributor to the development of hypertension. In spite of the low content of mitochondria and their low contribution to bioenergetics in VSMCs, recent studies have suggested that mitochondria play an important role in the regulation of VSMC function. However, the role of mitochondria in angiotensin II–induced VSMC dysfunction remains unknown. Here, we found that angiotensin II decreased the expression of Bcl-2-like protein 1 (Bcl-xL), a newly identified protein in inhibition of uncoupled proton flux in mitochondria through interaction with the β-subunit of ATP synthase, and uncoupled mitochondria in VSMCs both in vivo and in vitro. Overexpression of Bcl-xL restored the mitochondrial and VSMC function in response to angiotensin II treatment in vitro, suggesting that angiotensin II uncouples mitochondria through downregulation of Bcl-xL. Mechanistically, angiotensin II increased the expression of miR-140-5p, which targeted and downregulated Bcl-xL in VSMCs. Inhibition of miR-140-5p using antagomir-140-5p in vivo attenuated mitochondrial uncoupling and hypertension in angiotensin II-treated mice. These results suggested that upregulation of miR-140-5p uncouples mitochondria by targeting Bcl-xL in VSMCs in angiotensin II–induced hypertension, and miR-140-5p and Bcl-xL are potential targets for treatment of vascular dysfunction.